Development of a pea protein‐/chitosan‐based bioactive film using Aronia melanocarpa polyphenols as a bioactive ingredient. Issue 12 (23rd September 2022) - Nan, Xijun; Zhou, Quancheng; Ji, Wei; Chen, Xuanhong; Li, Jiayi; Wang, Honglei; Dong, Leichao; Meng, Xue; Sheng, Guihua
Abstract: The study was designed to develop a pea protein‐ (PP) and chitosan (CS)‐based bioactive composite film using purified Aronia melanocarpa polyphenols (AMP) as a bioactive ingredient (PP‐CS‐AMP). First, AMP was extracted and purified, and the antioxidant properties of AMP were tested, and the result indicated that AMP showed stronger antioxidant properties than vitamin C (Vc). Second, five kinds of PP‐CS film were developed: PP including unextruded pea protein (NEP), extrusion pea protein (EP), papain co‐extruded pea protein (PEP), neutral protease co‐extruded pea protein (NPEP), and double enzyme combined extrusion pea protein (DCEP). The five kinds of PP‐CS film were characterized and evaluated for various functions and properties; principal component analysis and membership evaluation were used to analyze the comprehensive scores of the films. It was observed that the NPEP‐CS film obtained the highest score. Extrusion and enzyme extrusion treatments improved the structure and properties of PP, and therefore enhanced the properties of PP‐CS film. Finally, NPEP‐CS‐AMP film was developed (AMP content 0, 4.0% and 8.0%, w/v) and tested for their performance, and the results suggested that the addition of 4.0% AMP gives the NPEP‐CS‐AMP film excellent physical and antioxidant properties. Novelty impact statement: Aronia melanocarpa polyphenols (AMP), as a bioactivity ingredient was firstly incorporated into pea protein (PP) ‐ chitosan (CS) film. Extrusion and enzyme extrusion can improve the structure and properties of PP, which is beneficial to improvement on the properties of PP‐CS film. NPEP‐CS‐AMP film exhibit excellent physical properties, structural performance and high antioxidant activity.